Studies of chromatographic separation and self-emulsification of crude oil. (17th January 2019) - Xie, Jianyong; Chu, Yanjie; Shi, Yan; Han, Xiaocheng; Li, Xu; Wang, Licheng; Guo, Yong
Abstract: The crude oil in Zhundong Oilfield has good self-emulsification phenomenon. In order to reveal the mechanism, the crude oil was divided into saturated hydrocarbon, unsaturated hydrocarbon, resin and asphalt by chromatographic method, and their contents are 40.09%, 11.19%, 48.05% and 0.67%, respectively. The effects of the petroleum components on self-emulsification were investigated. The results show that the resin has the most important effect on emulsification and plays the role of emulsifier. The saturated hydrocarbon and unsaturated hydrocarbon act as the basic oil and cannot be emulsified with the injection water without the resin emulsifier. Moreover, the resin content is very important, only when it is in a proper proportion, the system can be well self-emulsified. This work is useful for water flooding.